Metaphorisation and Metonimisation as Tools of Semantic Derivation (Based on English Coursebooks on Economics) - S. P. Anokhina (Дискурс профессиональной коммуникации, 2021)
The paper studies two types of indirect (secondary) nomination: simulative and indicative ones, exemplified by extracts from English coursebooks on economics. The similative nomination is actualised through functional transfer, which is interpreted as a separate kind of metaphor termed “actional metaphor”. The analysis of indicative nomination is focused on metonymy and synecdoche (as its closely related device), which is conditioned by the same transfer principle on the basis of an essential attribute. The semantic derivates are considered in sentences representing such logic thought form as definition, which allows to reveal the metaphoric and metonymic processes in the field of English economic terminology.The research discloses the interrelations between the analysed term models and their functions as designators for target and source domains on the one hand, and cognitive metaphor types (ontological and conceptual), on the other hand. The author comes to the conclusion that both types can have either simple or complicated structure. Similarly, there are simple and complicated metonymies. These phenomena make the peculiarities of the given economic discourse when considered from the angle of semantic derivation. The tendency to the uniform secondary semiotic code in term metaphor description can be viewed as another valid peculiarity of economic discourse.With regard to the indicative secondary nomination, the main findings are as follows: the metonymic lexis is organized as a chain opposition: terms and nomens – terms – terms and common lexis – common lexis. The mechanism of forming “mixed” kinds of the indirect nomination, i.e. metaphtonymy and synecdoche-metonymy, is revealed in the course of the context analysis. This leads the author to a hypothetical argument that it is the actional metaphor that underlies these mixed types of semantic derivatives.Both types of the secondary nomination have a systemic nature: metaphor is described in other system units; metonymies have field structure and are actualised through specific oppositions.